SARS-CoV-2 Infection and Active, Multiorgan, Severe cGVHD After HSCT for Adolescent ALL: More Luck Than Understanding? A Case Report - Zubarovskaya, Natalia; Hofer-Popow, Irene; Idzko, Marco; Haas, Oskar A.; Lawitschka, Anita (Frontiers in Pediatrics, 2022)
Graft-versus-host disease (GvHD) is a serious and complex immunological complication of haematopoietic stem cell transplantation (HSCT) and is associated with prolonged immunodeficiency and non-relapse mortality. Standard treatment of chronic GvHD comprises steroids in combination with other immunosuppressive agents. Extracorporeal photopheresis (ECP), with its immunomodulatory mechanism, is applied as part of steroid-sparing regimens for chronic GvHD. Immunocompromised, chronically ill patients are at particular risk of severe disease courses of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. T-cell immunity in SARS-CoV-2 infection is well described but the role of the humoral immune responses is not fully understood. This case report describes a moderate course of SARS-CoV-2 infection in a patient less than 9 months after HSCT who was suffering from active, severe, chronic GvHD treated with prednisone and ECP. Following HSCT from a matched unrelated donor to cure acute lymphoblastic leukaemia, the 25-year-old male patient experienced multiple infectious complications associated with cytopenia, B-cell dyshomeostasis and autoantibody production followed by development of severe chronic GvHD thereafter at day +212. The steroid-sparing treatment plan consisted of supportive care, topical treatment, prednisone and ECP. He was diagnosed with SARS-CoV-2 infection at day +252, experiencing loss of smell and taste as well as a cough. The patient’s oxygen saturation was between 94–97% on room air, and computed tomography images showed evolution of typical of SARS-CoV-2 infiltrates. In addition to cytopenia and immune dyshomeostasis, laboratory tests confirmed macrophage activating syndrome, transaminitis and Epstein-Barr virus viraemia. At that time, anti-SARS-CoV-2 monoclonal antibodies were not available in Austria and remdesivir seemed contraindicated. Surprisingly, despite severe lymphopenia the patient developed SARS-CoV-2-specific antibodies within 15 days, which was followed by clearance of SARS-CoV-2 and EBV with resolution of symptoms. Thereafter, parameters of immune dysregulation such as lymphopenia and B-cell dyshomeostasis, the latter characterized by elevated CD21low B cells and autoantibody expression, normalized. Moreover, we observed complete response of active chronic GvHD to treatment.